Exchange rate shocks and inflation comovement in the euro area - Danilo Leiva-Leon; Jaime Martínez-Martín; Eva Ortega (European Central Bank (ECB), 2020)
This paper decomposes the time-varying effect of exogenous exchange rate shocks on euro area countries in ation into country-specific (idiosyncratic) and region-wide (common) components. To do so, we propose a exible empirical framework based on dynamic factor models subject to drifting parameters and exogenous information. We show that exogenous shocks to the EUR/USD exchange rate account for over 50% of nominal EUR/USD exchange rate uctuations in more than a third of the quarters of the past six years, especially in turning point periods. Our main results indicate that headline in ation in euro area countries, and in particular its energy component, has become significantly more affected by these exogenous exchange rate shocks since the early 2010s, in particular for the region's largest economies. While in the case of headline in ation this increasing sensitivity is solely reliant on a sustained surge in the degree of comovement, for energy in ation it is also based on a higher region-wide effect of the shocks. By contrast, purely exogenous exchange rate shocks do not seem to have a significant impact on the core component of headline in ation, which also displays a lower degree of comovement across euro area countries.
Keywords: C32; E31; F31; F41; 330; Exchange Rate; Ination; Factor Model; Structural VAR model